Recycled bricks; a study on how recycled bricks can bring architectural qualities through the design of the façade - Mac, Tiffany (My University, 2024)
The majority of waste in Sweden is generated by the construction industry, where bricks from demolished buildings are often thrown away and ending up in landfills. This indicates that bricks are not a priority in the waste hierarchy. Despite the costs associated with waste management, these building materials are often in good condition for reuse in new projects. The current linear model in the construction sector leads to disposal of old materials and continues the production of new ones. This cycle begins with the extraction, production, consumption and disposal, resulting in a significant negative impact on the environment. According to the United Nations Agenda 2030, changes are necessary to achieve the outlined goals. Sustainable Development Goal 12 emphasizes responsible production and consumption, including Milestone 12.5 specifically focusing on waste reduction through prevention, reduction, recycling and reuse. Working towards these objectives will enable a shift from a linear to a more circular economy. Bricks, being a commonly used construction material with significant potential, could be used more sustainably. This can be achieved through three main approaches. Firstly, adopting gentler demolition methods that allows for a higher percentage of material to be reused compared to conventional methods. Secondly, integrating a demolition plan into the initial building project planning, which includes selecting the appropriate mortar for the specific bricks, thereby enhancing sustainability and overall efficiency. Lastly, as suggested in the report Facade Design Stages: Issues and Considerations (2019), reducing the variety of materials simplifies the demolition and sorting process, making it easier to reuse and recycle materials. Lastly, as suggested in the report Facade Design Stages: Issues and Considerations by Moghtadernejad (2019), This thesis aims to challenge preconceptions about recycled bricks by integrating life cycle assessment (LCA) through Environmental Product Declarations (EPD) with the life-cycle cost analysis (LCC), together with architectural qualities and criterias. Additionally, the project includes a design aspect that incorporates recycled bricks into the planning of a new building for a residential building situated on Tredje Långgatan in central Gothenburg, Sweden. The proposal arises from a comparison between two distinct recycling methods in comparison to using newly manufactured bricks.
Keywords: recycled bricks, circular economy, design principle, facade design, sustainability, construction details